2009
DOI: 10.1021/ja903531g
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Step, Formal [4 + 2] Approach toward Piperidin-4-ones via Au Catalysis

Abstract: An efficient, formal [4 + 2] synthesis of synthetically valuable piperidin-4-ones from secondary amines in two steps has been achieved via a key gold catalysis without the purification of tertiary amine intermediates. This reaction is selective toward the less-substituted alkyl group and shows moderate to excellent diastereoselectivities. Its synthetic potential in alkaloid synthesis is demonstrated in a highly diastereoselective synthesis of (+/-)-cermizine C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(67 citation statements)
references
References 25 publications
1
65
0
1
Order By: Relevance
“…We have recently reported a formal [4+2] approach for the synthesis of piperidin-4-ones [13] via a key gold catalysis [14][15][16][17][18][19][20][21][22][23]. In this two-step sequence (Scheme 1), a secondary amine is initially alkylated with but-3-ynyl tosy late in a S N 2 reaction; subsequent m-CPBA oxidation of the formed tertiary amine into the corresponding N-oxide is followed by Au(I)-catalyzed intramolecular oxidation of the alkyne moiety, yielding an -oxo gold carbene intermediate (i.e., A); a formal carbene insertion into the CH bond  to the nitrogen atom presumably via sequential hydride migration and cyclization leads to an overall 4+2 annulation between a secondary amine (a C1 + N1 unit) and a but-3-ynyl moiety (a C4 unit).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported a formal [4+2] approach for the synthesis of piperidin-4-ones [13] via a key gold catalysis [14][15][16][17][18][19][20][21][22][23]. In this two-step sequence (Scheme 1), a secondary amine is initially alkylated with but-3-ynyl tosy late in a S N 2 reaction; subsequent m-CPBA oxidation of the formed tertiary amine into the corresponding N-oxide is followed by Au(I)-catalyzed intramolecular oxidation of the alkyne moiety, yielding an -oxo gold carbene intermediate (i.e., A); a formal carbene insertion into the CH bond  to the nitrogen atom presumably via sequential hydride migration and cyclization leads to an overall 4+2 annulation between a secondary amine (a C1 + N1 unit) and a but-3-ynyl moiety (a C4 unit).…”
Section: Introductionmentioning
confidence: 99%
“…The tube was flamed dried under vacuum and flushed with N 2 three times. Under a N 2 atmosphere, an amide (0.1 mmol), [Au(PPh 3 )NTf 2 ] (5 mol %), freshly distilled CH 2 Cl 2 (1.6 mL), and a freshly prepared solution of MeSO 3 H in CH 2 Cl 2 (0.4 mL, 0.03 m) were sequentially added to the reaction tube. The reaction mixture was stirred at room temperature for 1 h before the reduction at the indicated reaction temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[2,3] For example, we have previously reported that piperidin-4-ones could be prepared in a two-step, [4+2] manner; [2a] however, the products were limited to those in which the ring nitrogen atoms contained hard-to-remove aliphatic substituents or benzyl groups which afforded low regioselectivities. To address this deficiency and develop a general and modular synthesis of N-unsubstituted piperidines, we envisioned that a gold-catalyzed cyclization of N-homopropargyl amide 2 would offer cyclic imidate 3, which could be chemoselectively reduced to afford a-amino ether A (Scheme 1).…”
mentioning
confidence: 99%
“…[2] This research area is rapidly growing owing to the unique properties of these metals in promoting two or more mechanistically distinct reactions in a tandem process to achieve molecular complexity from simple starting materials. [2] Among the various nucleophiles that are known to attack alkynes, nitrone, [3,4] nitro, [5] sulfoxide, [6] and amine N-oxide [7] groups are particularly interesting. Nucleophilic attack of these polar N + ÀO À groups on alkynes gives metal vinyl species [8] bearing a positively charged electrophilic center (A, Scheme 1; shown for endo cyclization only).…”
mentioning
confidence: 99%